IDEOLOGI DALAM MAJALAH ANAK DIGITAL - Shohiburrida, Muhammad (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
Digital children's magazines have now transformed into strategic socialization agents that not only entertain but also instill certain values ??and ideologies to shape children's social cognition and character. This study aims to deconstruct the ideological content of Bobo Digital magazine, focusing on identifying the ideas constructed, the mechanisms of representation, and the discursive strategies used to influence readers. Using a critical qualitative paradigm through Teun A. Van Dijk's Critical Discourse Analysis model, this study examines textual and visual data from the fiction and nonfiction sections throughout the 2020 edition. The findings indicate that the magazine consistently champions the ideology of multiculturalism, environmental conservation, health awareness (COVID-19), and social ethics. Operationally, this ideology is manifested through techniques of representation of reality and misrepresentation (such as marginalizing negative behavior) to assert moral boundaries. Discursive strategies are systematically implemented through macrostructure (thematic), superstructure (schematic), and microstructure (semantic, syntactic, stylistic, and rhetorical). It is concluded that Bobo Digital acts as a subtle instrument of hegemony that directs children's thinking patterns to align with the norms and expectations of the adult world. ABSTRAK Majalah anak digital kini bertransformasi menjadi agen sosialisasi strategis yang tidak sekadar menghibur, tetapi juga menanamkan nilai dan ideologi tertentu guna membentuk kognisi sosial serta karakter anak. Penelitian ini bertujuan untuk mendekonstruksi muatan ideologis dalam majalah Bobo Digital, dengan fokus pada identifikasi gagasan yang dibangun, mekanisme representasi, serta strategi diskursif yang digunakan untuk memengaruhi pembaca. Menggunakan paradigma kualitatif kritis melalui pisau bedah Analisis Wacana Kritis model Teun A. Van Dijk , penelitian ini mengkaji data tekstual dan visual dari rubrik fiksi serta nonfiksi sepanjang edisi tahun 2020. Temuan menunjukkan bahwa majalah ini secara konsisten memperjuangkan ideologi multikulturalisme, pelestarian lingkungan, kesadaran kesehatan (Covid-19), serta etika sosial. Secara operasional, ideologi tersebut dimanifestasikan melalui teknik representasi realitas dan misrepresentasi (seperti marginalisasi perilaku negatif) untuk menegaskan batasan moral. Strategi pewacanaan diterapkan secara sistematis melalui elemen makrostruktur (tematik), superstruktur (skematik), dan mikrostruktur (semantik, sintaksis, stilistik, retoris). Disimpulkan bahwa Bobo Digital berperan sebagai instrumen hegemoni halus yang mengarahkan pola pikir anak agar selaras dengan norma dan ekspektasi dunia orang dewasa.